Pemahaman Bidan tentang Permenkes RI No. 1464/Menkes/Per/X/2010 tentang Ijin dan Penyelenggaraan Praktik Bidan - Puji Hastuti; Diki Retno Yuliani; Rusmini Rusmini (Jurnal LINK, 2015)
This study aimed to find out midwives’ understanding in Banyumas regency on the Regulation of Ministry of Health Number. 1464/Menkes/Per/X/2010 about License and Implementation of Midwifery Practice. Descriptive research with cross sectional design was used as study design. The accidental sampling technique was used in this reseach. Research result shows that midwives’ understanding the regulation are: 55% in the category from high to adequate of enough and 3% in the category of low and less. We recommend midwifes to be more active in seeking information and for further research should using a better sampling techniques with other variables such as the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number 1464/Menkes/Per/X/2010 about License and Implementation of midwifery practices in Banyumas.